2018
DOI: 10.1007/s00253-018-8794-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface proteins involved in the adhesion of Streptococcus salivarius to human intestinal epithelial cells

Abstract: The adhesion properties of 14 Streptococcus salivarius strains to mucus (HT29-MTX) and non-mucus secreting (Caco-2/TC7) human intestinal epithelial cells were investigated. Ability to adhere to these two eukaryotic cell lines greatly differs between strains. The presence of mucus played a major factor in adhesion, likely due to high adhesiveness to mucins present in the native human mucus layer covering the whole cell surface. Only one S. salivarius strain (F6-1), isolated from the feces of a healthy baby, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 98 publications
(110 reference statements)
1
32
0
Order By: Relevance
“…High auto-aggregation was also reported for the strains of L. casei and L. fermentum, ranging from 60.97% to 96.18% [19]. Some studies reported a correlation between aggregation and adhesion capacity [41]; on the contrary, other studies did not demonstrate such a correlation and link between these two properties [13]. According to our results, strains having good adhesion capacities to the cell culture, usually had good auto-aggregation properties.…”
Section: Strainsupporting
confidence: 72%
See 4 more Smart Citations
“…High auto-aggregation was also reported for the strains of L. casei and L. fermentum, ranging from 60.97% to 96.18% [19]. Some studies reported a correlation between aggregation and adhesion capacity [41]; on the contrary, other studies did not demonstrate such a correlation and link between these two properties [13]. According to our results, strains having good adhesion capacities to the cell culture, usually had good auto-aggregation properties.…”
Section: Strainsupporting
confidence: 72%
“…Bacterial adhesion is based on non-specific physicochemical interactions between two surfaces, and therefore, it is usually associated with the characteristics of the cell surface. The adhesion ability to mucin-producing cells is better than to non-mucus-producing ones; thus, the presence of mucus seems to play a major role in adhesion [13]. Accordingly, to compare adhesive properties of bacteria in vitro, we used a co-culture of non-mucus-secreting Caco-2 cells and mucus-secreting HT-29-MTX cells in the ratio 9:1 as a model of intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations